Enhancing Arabic Speaking Skills Through the Stand-Up Category Method: A Dynamic Approach to Engaging Learning - Hasyim, Mochamad; Syarifuddin, Syarifuddin; Hidayati, Nurul (STUDI ARAB, 2024)
This study aims to improve students' Arabic speaking skills through the application of the stand-up category method. Conducted at Madrasah Aliyah Darut Taqwa Purwosari Pasuruan, the research involved 26 eleventh-grade students. A classroom action research (CAR) approach was implemented using a quantitative method, consisting of two cycles with four stages: planning, action, observation, and reflection. Data collection techniques included observations, interviews, and pre-test and post-test assessments. The results indicate a significant improvement in students' speaking skills. The percentage of students achieving the minimum competency criteria increased from 38.46% in the pre-cycle to 57.69% in Cycle I and further to 84.62% in Cycle II. Additionally, student engagement and participation improved, with increased attention to lessons, active responses to questions, and reduced passivity. The study concludes that the stand-up category method effectively enhances Arabic speaking skills by creating an interactive and stimulating learning environment. This method is recommended for educators seeking innovative strategies to foster confidence and active participation in language learning.